Chemokine (C‐X‐C motif) ligand 13 promotes intrahepatic chemokine (C‐X‐C motif) receptor 5+ lymphocyte homing and aberrant B‐cell immune responses in primary biliary cirrhosis. Issue 6 (18th March 2015) - Li, Yongyin; Wang, Weibin; Tang, Libo; He, Xuanqiu; Yan, Xin; Zhang, Xiaoyong; Zhu, Youfu; Sun, Jian; Shi, Yongquan; Ma, Xiong; Mackay, Ian R.; Gershwin, M. Eric; et al.
<x xml:space="preserve">Abstract</x> The serological hallmark of primary biliary cirrhosis (PBC) is the presence of high titer and specific antimitochondrial antibodies (AMAs). Although there is no global immune defect in patients with PBC, there is widespread dysregulated B‐cell function, including increased sera levels of immunoglobulin M and enhanced B‐cell responses to cytosine‐phosphate‐guanine stimulation. The mechanisms involved in this B‐cell dysfunction have remained unknown. To address this issue, we focused on identifying the frequencies of B‐cell subsets in patients with PBC and the mechanisms that lead to B‐cell dysregulation, including the relationships with chemokine (C‐X‐C motif) receptor 5 (CXCR5)+CD4+T cells. Herein, we report that elevations of both serum and intrahepatic interleukin‐21 (IL‐21) were found in patients with PBC and, in particular, promoted B‐cell proliferation, signal transducer and activator of transcription 3 phosphorylation and AMA production in vitro. More important, upon stimulation with recombinant E2 subunit of pyruvate dehydrogenase complex, CXCR5+CD4+T cells in PBC produced higher levels of IL‐21 than healthy controls. Additionally, sorted CXCR5+CD4+T cells increased production of AMAs by autologous CD19+B cells. Indeed, elevated expression of intrahepatic chemokine (C‐X‐C motif) ligand 13 (CXCL13), a key chemokine of CXCR5+ cells, was uniquely found within the portal tracts in PBC, accompanied by infiltrates of CD4+, CXCR5+, CD19+, and CD38+ cells. Conclusion: CXCL13 promotes aggregation of CD19+B cells and CXCR5+CD4+T cells, which directs the aberrant AMA response by IL‐21. These data have implications for potential immunotherapy and also reflect the unique lymphoid biology in liver of PBC. (Hepatology 2015;61:1998‐2007)